Juegos tradicionales como estrategia de enseñanza y aprendizaje en los niños de 2do año básica de la Unidad Educativa 3 de Noviembre, de Nuevo Zapotal - Acosta Vera, Milly Jorlendy (2023)
The present research was developed under the perceptions that consider traditional games as a teaching alternative that develops the psychosocial and motor spheres of students in early childhood within educational contexts. The main objective has been to determine the importance of the application of traditional games as a teaching and learning strategy in children in the 2nd year of Basic Education at the 3 de Noviembre Educational Unit, in Nuevo Zapotal. Methodology: A research with a qualitative and descriptive approach was used, considering investigative antecedents and relating them to reality. An intentional sample of teachers was chosen through non-probabilistic sampling to collect information according to the application of a structured questionnaire of questions (interview; where general knowledge and the methodology of application of traditional games were assessed. Results: It was possible know that the teachers of the Educational Unit 3 de Noviembre, of Nuevo Zapotal, consider the application of traditional games in physical education classes to be relevant because through them the culture and tradition of the community is strengthened and they improve social behavior; however, lack the appropriate methodology for its application as they are not specialists. Conclusions: The application of traditional games as a teaching strategy in the childhood stage are considered as special means for the development of the socio-affective and motor spheres of the child.